Gentrificaton in the former black townships - the case of Soweto in South Africa. - Sibiya, Philile Nkosikhona (My University, 2013)
In South Africa, the term ‘former black township’ refers to areas that were designated for people who were classified as Africans, Coloureds or Indians under the apartheid regime. These areas were severely underdeveloped and were deliberately cut off from the mainstream economy. They were characterized by “racial segregation, exclusion and the marginal provision of services and economic opportunities”. Since 1994, the democratic government of South Africa has initiated a number of developments to improve these areas and provide them with the same services and amenities previously found in the former ‘white’ areas (Lester et.al, 2009: 6). This has resulted in an increase in property prices and an influx of a black middle class. This raises a number of questions around the possibility of gentrification in the former black townships. It also raises questions around the possibility of a relationship between the increase in property prices, the influx of higher income people and the out-migration of original residents. The research focused on a case study, Soweto Township, with the aim of investigating whether it is experiencing any of the characteristics associated with gentrification; and whether there is a link between urban renewal, increase in property prices, the in-migration of a middle class; and the out-migration of original residents. Findings from the research have shown that even though the township is experiencing all the above, there has been no evidence of a link that would suggest the occurrence of gentrification in the area. The township is merely experiencing urban regeneration, with the increase in property prices and the influx of higher income groups being ripple effects of the former. Furthermore, a link has not been established between these three variables and the out-migration of original residents.